2010
DOI: 10.1007/s12264-010-9182-5
|View full text |Cite
|
Sign up to set email alerts
|

UNC-64 and RIC-4, the plasma membrane-associated SNAREs syntaxin and SNAP-25, regulate fat storage in nematode Caenorhabditis elegans

Abstract: Objective To investigate whether genes required for synaptogenesis and synaptic function are also involved in fat storage control in Caenorhabditis elegans. Methods Fat storage was examined in mutants of genes affecting the synaptogenesis and synaptic function. In addition, the genetic interactions of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 37 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…4a ). Considering the fact that Nile Red can also be used to label fat storage 46 , we further analyzed the triglyceride content of nematodes. LAB pretreatment or GO (100 mg/L) exposure did not significantly influence the triglyceride content compared with control in wild-type nematodes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4a ). Considering the fact that Nile Red can also be used to label fat storage 46 , we further analyzed the triglyceride content of nematodes. LAB pretreatment or GO (100 mg/L) exposure did not significantly influence the triglyceride content compared with control in wild-type nematodes ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among eight syntaxin genes in the C. elegans genome, unc-64 encodes a mammalian syntaxin 1A homologue and is involved with presynaptic function in the nerve systems ( Saifee et al , 1998 ). The unc-64 gene is also expressed in many secretory tissues, including the intestine ( Wu et al , 2010 ). Syntaxin gene syn-1 , the product of which is most similar to syntaxin 1, is expressed in the intestine and is involved in defecation behavior ( Yamashita et al , 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that GO exposure could not alter the fat storage in wild-type nematodes [ 28 ]. Considering the fact that the Nile Red can also used to label the fat storage [ 58 ], our results suggest that PKC-3 is required for the regulation of intestinal permeability in nematodes.
Fig.
…”
Section: Resultsmentioning
confidence: 96%
“…Sudan Black staining method was performed as described previously [ 58 ]. The examined nematodes were washed in M9 buffer and fixed with 1% paraformaldehyde.…”
Section: Methodsmentioning
confidence: 99%